2017
DOI: 10.1002/adsc.201700329
|View full text |Cite
|
Sign up to set email alerts
|

α‐Keto Thioesters as Building Blocks for Accessing γ‐Hydroxybutenolides and Oxazoles

Abstract: Abstractα‐Keto thioesters, with two electrophilic carbon centres, have been found to react differently with β‐keto esters and isocyanoacetates. They undergo base induced Knoevenagel‐type condensation on the keto carbonyl group with β‐keto esters, followed by intramolecular cyclization and water addition leads to highly substituted γ‐hydroxybutenolides. On the other hand, substituted oxazole derivatives have been obtained using isocyanoacetates via nucleophilic displacement on the thioester carbonyl followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Building on their experience with cascade sequences or successive reactions of α‐ketothioesters adorned with two reactive centres, they developed two independent methodologies for the reaction of α‐ketothioesters with different active methylene compounds, such as β‐ketoesters 56 a and isocyanoacetates 56 b , as shown in Scheme 32 [61] . They found that the substrates exhibited different site selectivity in reaction with these active methylene compounds.…”
Section: Reactions Of α‐Ketothioestersmentioning
confidence: 99%
“…Building on their experience with cascade sequences or successive reactions of α‐ketothioesters adorned with two reactive centres, they developed two independent methodologies for the reaction of α‐ketothioesters with different active methylene compounds, such as β‐ketoesters 56 a and isocyanoacetates 56 b , as shown in Scheme 32 [61] . They found that the substrates exhibited different site selectivity in reaction with these active methylene compounds.…”
Section: Reactions Of α‐Ketothioestersmentioning
confidence: 99%
“…Das and Mal employed α ‐keto thioesters 108 , with two electrophilic carbon centers, as component for nucleophilic displacement on the thioester carbonyl followed by intramolecular cyclization with isocyanoacetates 1 . [ 66 ] Substituted oxazole derivatives 109 were obtained using K 2 CO 3 as a base in DMF with the yields of 55–93 %. To determine whether α ‐keto ester could be also available substrate in this cyclization reaction, authors performed the reaction of oxo esters 110 with isocyanoacetates 1 .…”
Section: [3+2]‐cycloaddition Of Activated Methylene Isocyanidesmentioning
confidence: 99%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 Thiocyanate and cyanate salts have been recognized as one of the most efficient and versatile reagents for accessing diverse heterocycles. [6] In the course of our continuing efforts, [7] the reactivity of aketo thioesters with these salts was investigated. We observed that a-keto thioesters underwent nucleophilic displacement with thiocyanate/cyanate on the thioester carbonyl, followed by intermolecular thiolate addition to the carbonyl carbon, and subsequent intramolecular CÀO heterocyclization to afford 2thioxooxazolidin-4-one and oxazolidine-2,4-dione derivatives, respectively (Scheme 1c).…”
Section: -Thioxooxazolidin-4-onementioning
confidence: 99%